Triple Higgs coupling effect on h0→bb¯ and h0→τ+τ− in the 2HDM - A. Arhrib; R. Benbrik; J. El Falaki; W. Hollik (Physics Letters B, 2017)
We study the one-loop electroweak radiative corrections to h0→bb¯ and h0→τ+τ− in the framework of two Higgs doublet Model (2HDM). We evaluate the deviation of these couplings from their Standard Model (SM) values. h0→bb¯ and h0→τ+τ− may receives large contribution from triple Higgs couplings h0H0H0, H0h0h0, h0A0A0 and h0H+H− which are absent in the Standard Model. It is found that in 2HDM, these corrections could be significant and may reach more than 12% for not tow heavy H0 or A0 or H±. We also study the ratio of branching ratios R=BR(h0→bb¯)/BR(h0→τ+τ−) of Higgs boson decays which could be used to disentangle SM from other models such as 2HDM.